Collision avoidance cooperative attack with multiple pursuers based on bearing-only measurements. Issue 1 (January 2020) - Hu, Zilun; Yang, Jianying
Abstract: This paper provides a novel collisions avoidance cooperative attack method for multiple pursuers system based on bearing-only measurements. In the cooperative attack problem, the control algorithm must drive all of the attackers to converge to the desired position (target). However, the traditional consensus protocol based on the relative position information may cause the intervehicle collisions before the attackers can hit the target. To solve this issue, a distributed cooperative consensus control algorithm is proposed. Under this algorithm the potential collisions are proved to be avoided while the pursuers can achieve the final attack. Further more, considering the relative distance information is unavailable for some types of the pursuers to get, a control algorithm based on bearing-only measurements is proposed by referencing the distributed localization algorithm used in the sensors network. The advantages of this method are summed up as fully distributed, collisions avoidance, and bearing-only measurements. Finally, the effectiveness of the results is illustrated by numerical simulation.